Fighting Hypoxia to Improve PDT - Ludivine Larue; Bauyrzhan Myrzakhmetov; Amina Ben-Mihoub; Albert Moussaron; Noémie Thomas; Philippe Arnoux; Francis Baros; Régis Vanderesse; Samir Acherar; Céline Frochot (MDPI AG, 2019)
Photodynamic therapy (PDT) has drawn great interest in recent years mainly due to its low side effects and few drug resistances. Nevertheless, one of the issues of PDT is the need for oxygen to induce a photodynamic effect. Tumours often have low oxygen concentrations, related to the abnormal structure of the microvessels leading to an ineffective blood distribution. Moreover, PDT consumes O2. In order to improve the oxygenation of tumour or decrease hypoxia, different strategies are developed and are described in this review: 1) The use of O2 vehicle; 2) the modification of the tumour microenvironment (TME); 3) combining other therapies with PDT; 4) hypoxia-independent PDT; 5) hypoxia-dependent PDT and 6) fractional PDT.